Great Mining Camps of Canada 3. The History and Geology of the Cariboo Goldfield, Barkerville and Wells, BC - Brown, Atholl; Ash, Chris (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2009)
SUMMARY The discovery of placer gold deposits in the Cariboo in 1860, and the immediate realization of their importance, were directly responsible for the establishment of the Province of British Columbia, allowing Canada to expand from ‘Sea to Shining Sea.’ Later, in the early 1930s, the new lode gold mines helped rescue the province from bankruptcy during the Great Depression. The Cariboo Goldfield is one of the longest continuously productive mining camps in Canada (nearly 150 years). The Cariboo Goldfield, like the California Goldfield, manifests two styles of mineralization: 1) primary lode gold deposits, and 2) secondary placer deposits. In plan, the zone of lode deposits trends linearly about 6 km in a northwest–southeast direction, within an inverted boot-shaped cluster of placer deposits having a surface area of about 250 km2. Three zones of rich placer creeks also trend northwest– southeast within the goldfield, the most northeasterly of which envelopes the known lode trend. The Cariboo Goldfield encompasses two dominant rock domains–an upper or hanging-wall domain of late Paleozoic ophiolitic rocks, part of Slide Mountain Terrane, and a more widespread, lower or foot-wall domain of late Proterozoic to Paleozoic continental margin meta-sedimentary rocks, part of the Barkerville Terrane. In cross-section, the lode deposits are located in a sub-horizontal, terrane-bounding fault (suture or high-strain zone), which separates the hanging-wall and footwall domains. The vertical extent of the mineralized zone below this suture is half a kilo-metre or less. Gold occurs in both pyritic quartz veins and pyritic replacement deposits; the mineralogy of the ore is simple: gold-bearing (auriferous) pyrite and minor amounts of other sulfide minerals. Three lode mines in the goldfield are from southeast to northwest, the Cariboo Gold Quartz, Island Mountain and Mosquito Creek mines. Combined production from these mines between 1933 and 1987 is about 38.3 million grams (g) (1.23 million troy ounces) of gold and 3.16 million g (101 439 troy ounces) of silver, which would be worth more than one billion dollars at current prices (~US$900 gold). Major placer deposits are located largely along creeks in the Goldfield mostly lying in gutters on bedrock overlain by Late Tertiary gravels but gold is also redistributed within overlying glacial sediments. Gold nuggets exhibit diverse shapes, from irregular and drusy to rounded and hammered, indicative of varied histories of transport. Average fineness ranges from 830 to 950 [gold to gold+silver, pure gold = 1000]. Since 1860, placer mines probably produced more than 118.2 million g (3.8 million troy ounces) worth about 3.4 billion dollars at current prices. Adventuresome placer miners reached the south end of the Goldfield in the winter of 1860 and the major producing creeks were all discovered during the following year. Initial mining took place in shallow deposits along creeks but within a year some mining was underway in water saturated gravels to depths of 20 m. Production peaked in 1863 but has continued at diminished rates until today. As placer production tailed off, great efforts went into the search for lode deposits. Many mineralized, pyritic quartz veins were found with very fine-grained gold contained within pyrite, but quartz veins containing nugget gold typical of that found in the placers remained elusive. In spite of provincial government assistance by providing milling and roasting facilities to process the lode deposits, the technology of the day was inadequate to make the deposits economic. The lodes were not viable until cyanide treatment became available and the price of gold rose. The Cariboo Gold Quartz mine opened in January 1933 and Island Mountain in November 1934. The Cariboo Gold Quartz purchased the Island Mountain mine in 1959 and both mines continued producing until 1967 when they closed because of unfavourable economics. Higher gold prices resulted in the Mosquito Creek mine coming into production in 1980 and continuing until 1987, after prices had receded. Recent high gold prices have again stimulated significant exploration. Like all gold rushes, the Cariboo has had a cast of strong and interesting characters. Four of the most memorable include: Billy Barker, an early placer miner; Bill Hong, a later Chinese placer miner; Amos Bowman, the first geologist; and Fred Wells, a prospector and mining entrepreneur during the heyday of lode mining. The village of Barkerville, named after Billy Barker, is now the site of a provincial park and museum dedicated to the gold rush, and the nearby town of Wells, named after Fred Wells, now functions mainly as a base for seasonal tourism, some exploration, and minor placer mining.